DISTRIBUSI PENDAPATAN RUMAH TANGGA PETANI KARET DI KENAGARIAN SUNGAI LANGKOK KECAMATAN TIUMANG KABUPATEN DHARMASRAYA - Malaras, Ongky; Malinda, Yola; Afriza, Rina (Pendidikan Ekonomi, 2014)
ABSTRACT This study aims to identify and analyze the distribution of household income Kenagarian rubber farmers in the River District of Tiumang Langkok Dharmasraya . The method used in this research is descriptive method . The study population was all farm households in the river kenegarian langkok tiumang Dharmasraya districts totaling 548 households. The sampling technique mengguanakan purposive sampling technique . Data were collected through a questionnaire which has been valid and reliable test . The analysis technique used is deskriktif , Correlation Coefficient , and the Gini ratio . Correlation coefficient to see there is a relationship between the land revenue , with revenue production , pengethuan with income , and capital with the relationship . Testing done with SPSS version 16.0 . Gini ratio to look high and low income individuals and functional disrtibusi in villages Langkok River districts Tiumang Dharmasraya district .The results of this study indicate that : 1 . Existence of a weak relationship between the area of Land with income . 2 . Existence of a strong relationship between the production of income . 3 . Meanwhile, knowledge and capital to have only a very weak relationship to income . 4 . Results of this study show the condition of the household income distribution of rubber farmers with the results of Gini ratio of 0.3902 or 0.39 , which means the distribution of personal income in the category of rubber farmers inequality being . The author suggested to the national and local governments are expected to organize well in providing credit counseling and assistance in the maintenance and purchase of seeds and tools that can help increase the production of rubber so that the right target and to the people who really need .